(untitled) (Semiárida, 2017)
Our objectives were to (1) determine the effects of light on seed germination of 2 populations (P1, P2) of Pappophorum vaginatum, and (2) compare the germination responses between these populations. Because of this, two studies were conducted. The first study evaluated the effects of 2 light conditions (L0=darkness, and L1=14 h light) on the cumulative germination (%) after 4, 8, 15 and 19 days from imbibition. The second study was conducted only under L1 conditions, and it evaluated the (a) cumulative germination, (b) germination speed index, (c) time to 50% of cumulative germination (T50), (d) percentage of empty spikelets (i.e., without cariopsis), and percentage spikelets with imbibed, but not germinated cariopsis after 19 days from imbibition of seeds. Pappophorum vaginatum was the dominant species in both study communities, but total, live plant cover was 37.5% in community 1, and 62.5% in community 2. Both populations were sensitive to light. After 19 days from imbibition there was a significant, positive effect of light on cumulative germination. In the second study, cumulative germination and germination speed index were greater (p≤0.01) in P1 than in P2. At the same time, T50 and the percentage of spikelets with imbibed, but not germinated cariopsis, were greater (p≤0.01) in P2 than in P1; no differences were found in the percentage of empty spikelets. Our results demonstrated that light was important for seed germination in P. vaginatum, and that the timing for initiating germination as a response to light differed between the two study P. vaginatum populations. DOI: http://dx.doi.org/10.19137/semiarida.2016(02).9-18